Gallery - Brocas, William, ca. 1794-1868 (1814)
Visitors to an art exhibition at the premises of Daniel Egan, carver, gilder and art dealer (listed at Ormond Quay 1848-1925)
Inscribed in pencil on verso: 26 Lower Ormond Quay
Title inscribed in pencil l.c.
Formerly 1964 (TX) 13
Attributed to William Brocas RHA
Keywords: Egan, Daniel; Art exhibitions -- Ireland -- Dublin -- 1810-1870; Commercial art galleries -- Ireland -- Dublin -- 1810-1870; Drawings -- Irish -- 1810-1870; Pencil works -- Irish -- 1810-1870